2000
DOI: 10.1016/s0747-5632(99)00056-4
|View full text |Cite
|
Sign up to set email alerts
|

Bystander intervention in computer-mediated communication

Abstract: Chat groups' were observed to demonstrate that the theoretical framework proposed in Latane and Darley's theory of bystander intervention (Latane & Darley, 1970; The unresponsive bystander: why doesn't he help? New York, NY: Appleton-Centruy Crofts) can also be utilized to explain and predict intervention in computer-mediated communication. Speci®c hypotheses focused on the relations between the amount of time it took a bystander to give assistance with the gender of the individual seeking help, the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
3
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 9 publications
4
69
3
1
Order By: Relevance
“…Although initial research into the diffusion effect dealt with offline emergency situations (Darley & Latané, 1968a), similar effects have recently been observed online, in message board requests to strangers (Markey, 2000) and email requests from a university colleague (Blair et al, 2005). Also, research has shown that the diffusion of responsibility effect is likely stronger in situations where there is low potential for immediate danger to the victim (Fisher et al, 2006).…”
Section: The Present Studymentioning
confidence: 88%
See 2 more Smart Citations
“…Although initial research into the diffusion effect dealt with offline emergency situations (Darley & Latané, 1968a), similar effects have recently been observed online, in message board requests to strangers (Markey, 2000) and email requests from a university colleague (Blair et al, 2005). Also, research has shown that the diffusion of responsibility effect is likely stronger in situations where there is low potential for immediate danger to the victim (Fisher et al, 2006).…”
Section: The Present Studymentioning
confidence: 88%
“…In one example, researchers posted requests for help in a public, online message board. Message board participants were more likely to quickly respond to the requests when there were fewer active, online posters on the board, particularly when the bystander was not asked directly by name for help (Markey, 2000). Another study found that the likelihood of helping in response to an email request declined when the email message indicated that multiple recipients were contacted (Blair, Thompson, & Wuensch, 2005).…”
Section: Diffusion Of Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating the results and methods traditionally used by social and personality researchers, a better understanding of interactions in Internet chat rooms can be achieved (Markey, 2000). To accomplish this, the Social Relations Model (SRM) (Kenny, 1994) is used to explore personality perception in Internet chat rooms by examining (a) the degree of consensus and assimilation for traits within the FFM during one-on-one and group interactions, (b) the agreement and differences between how targets see themselves and how judges perceive them, and (c) whether individuals' personality and chat room experience can predict how much they are liked by judges.…”
mentioning
confidence: 99%
“…An important task for a vital online community is to motivate people to join and contribute over a long period of time. This also makes an online community more interesting for non-members and lowers the bar to passively follow and finally to join it (Markey, P. M. 2000).…”
Section: Introductionmentioning
confidence: 99%